Дослідження методів відстеження телефонів за допомогою GPS та через відправку пакетів даних за назвою мережі - Запара, О. С. (ХНУРЕ, 2024)
The object of research is methods of tracking phones using GPS and sending data packets by network name. The purpose of the work is to study methods for tracking phones using GPS and by sending data packets by network name to study comparative performance characteristics and implementation of similar methods. Methods and methods of tracking smartphones, ways of their implementation and final results for comparative characteristics are considered in the work. As a result of the work, the methods of tracking phones using GPS and sending data packets by network name were investigated, their implementation and methods of reproduction in the program for their use, a comparative characteristic of similar methods and their implementation was developed.
Keywords: gpsGPS; пакет даних